PENGARUH PENERAPAN ELECTRONIC HUMAN RESOURCE MANAGEMENT (e-HRM) TERHADAP KINERJA KARYAWAN DI ERA SOCIETY 5.0 - Khairunnisa Rahmi; Khuzaini; Syahrial Shaddiq (PT. Saha Kreasi Indonesia, 2025)
The development of digital technology in the Society 5.0 era has changed the paradigm of human resource (HR) management in modern organizations. One form of innovation that is growing rapidly is the implementation of Electronic Human Resource Management (e-HRM), namely the use of information technology to support key HR functions such as recruitment, training, performance appraisal, and employee administration. This study uses a descriptive qualitative approach with a literature review method to explore and describe the influence of e-HRM on employee performance based on the results of previous research. The results of the study indicate that e-HRM plays a significant role in increasing the efficiency, transparency, and accuracy of HR processes and encourages improved employee performance through automation, data-based decision making, and strengthening digital communication. However, the success of e-HRM implementation is greatly influenced by organizational readiness, HR digital competence, and support for a work culture that is adaptive to technological change.